2021
DOI: 10.1083/jcb.202007195
|View full text |Cite
|
Sign up to set email alerts
|

CENP-A overexpression promotes aneuploidy with karyotypic heterogeneity

Abstract: Chromosomal instability (CIN) is a hallmark of many cancers. Restricting the localization of centromeric histone H3 variant CENP-A to centromeres prevents CIN. CENP-A overexpression (OE) and mislocalization have been observed in cancers and correlate with poor prognosis; however, the molecular consequences of CENP-A OE on CIN and aneuploidy have not been defined. Here, we show that CENP-A OE leads to its mislocalization and CIN with lagging chromosomes and micronuclei in pseudodiploid DLD1 cells and xenograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 113 publications
3
45
0
Order By: Relevance
“…Increased ectopic CENP-A directly correlates with mitotic defects [46,116]. As mentioned above, overexpressed CENP-A can weaken the endogenous kinetochore [46,99] royalsocietypublishing.org/journal/rsob Open Biol. 11: 210189…”
Section: Cenp-a Mislocalization and Cancersmentioning
confidence: 86%
See 1 more Smart Citation
“…Increased ectopic CENP-A directly correlates with mitotic defects [46,116]. As mentioned above, overexpressed CENP-A can weaken the endogenous kinetochore [46,99] royalsocietypublishing.org/journal/rsob Open Biol. 11: 210189…”
Section: Cenp-a Mislocalization and Cancersmentioning
confidence: 86%
“…These cells exhibit lagging chromosome, micronuclei formation and abnormal mitotic exit [34,45,46]. It has been shown that overexpression of CENP-A in human cells causes reduced kinetochores in native centromeres and unstable kinetochore-microtubule interaction, which may contribute to the cellular defects in these cells [46,99]. Overexpression of CENP-A also leads to misregulation of gene expression, which can also contribute to the defects [99][100][101].…”
Section: Mislocalization Of Cenp-a Has Deleterious Effect On Chromosome Segregationmentioning
confidence: 99%
“…Interestingly, High-level CENPA in ccRCC is consistent with the CIN in cancer. In addition, CENPA overexpression promotes aneuploidy with karyotypic heterogeneity [ 36 ]. Therefore, we deduced that chromosomal aneuploidy caused by CENPA overexpression is an important cause of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from human cells shows that CENP-A incorporation in ectopic sites leads to the recruitment of other centromeric components. In cancer cells, CENP-A overexpression can be detrimental, leading to neocentromere formation, chromosomal instability and growth advantage, increasing tumour malignancy [28].…”
Section: Epigenetics Approaches To Explore the Architecture Of Centromeric Chromatinmentioning
confidence: 99%
“…The molecular consequences of CENP-A overexpression in cancer cells are still unclear [25][26][27]. However, CENP-A overexpression drives chromosomal instability and aneuploidy, as shown in a cancer cell line and in a xenograft mouse model [28].…”
Section: Introductionmentioning
confidence: 99%